Finite element - Multi-domain boundary element method for hydroelastic analysis of large floating pontoons with perforated plates. (15th February 2022) - Nguyen, H.P.; Wang, C.M.
Abstract: This paper presents a Finite Element-Multi-Domain Boundary Element (FE-MDBE) method for the hydroelastic analysis of large floating pontoon structures with perforated plates. The structure is modelled by the shell theory while the fluid motion is modelled by using the linear wave theory. When fluid flows through the perforated plates, it is assumed that the velocity is unchanged but the fluid pressure drops by an amount that is determined by an empirical relationship involving the fluid velocity and the porosity of the perforated plate. The equations governing the fluid-structure interaction are solved by using the Finite Element Method (FEM) and Multi-Domain Boundary Element Method (MDBEM). In the MDBEM, the fluid domain is imaginarily decomposed into interior and exterior domains so as to avoid the singularity that arises when using the conventional BEM for solving hydroelastic problems involving thin submerged structures. The proposed FE-MDBE method is verified by comparing its results with experimental results obtained for a flexible platform and a fixed cylinder with perforated sidewall. The verified method is used for the hydrodynamic and hydroelastic analyses of floating breakwaters and large floating platforms with vertical perforated plates at their fore and/or aft. Highlights: Finite Element – Multi-Domain Boundary Element Method is proposed. Numerical results are compared with available experimental data. Hydroelastic analysis of large floating platforms with perforated plates. Hydrodynamic/hydroelastic analyses of floating breakwaters with perforated skirt plates.